Pemberdayaan Siswa PMR Sebagai Kader Anti Anemia dalam Upaya Pencegahan Anemia Prakonsepsi - Nisa, Juhrotun; Chikmah, Adevia Maulidya; Andari, Istiqomah Dwi; Muslich, Annisa Fadillah; Amalia, Elfa Zulfatun (Universitas Nusantara PGRI Kediri, 2020)
The World Health Organization (WHO) targets a 50% reduction in the incidence of anemia by 2025, while adolescents are still in the vulnerable group for anemia, because the peak of iron absorption occurs in adolescence. The high incidence of anemia is not balanced by the existence of screening for anemia, even teenagers tend not to have their hemoglobin levels checked. Delay in handling anemia affects when a woman has a pregnancy, so that it can cause bleeding complications during childbirth, giving birth to babies with low body weight, infants growing with stunting and so on. The purpose of this community service is to conduct training and empower students who are active in the Youth Red Cross (PMR) activities as cadre of anti-anemia in the effort to prevent preconception anemia by providing knowledge about anemia, how to detect early anemia events through physical examination and examination of hemoglobin. The activity was carried out in one of the Tegal City Vocational Schools on January 28-29, 2020 followed by Class X and XI students who were active in the Youth Red Cross extracurricular activities (PMR), with a total of 20 people (4 class XI and 16 class X).